2018
DOI: 10.1016/j.ijsu.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of major postoperative complications on long-term outcomes following curative resection of colon cancer

Abstract: The development of major complications following colectomy for colon cancer has a negative impact on long-term oncologic outcomes, especially in stage III disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…To our knowledge, there is no literature regarding residual tumour classification as a risk factor for recurrence in colon cancer, although it has been related to poor outcomes (Quintana et al, 2016; Yabusaki, Nashimoto, Matsuki, & Aizawa, 2014). Third, ASA grade, a variable related to surgical risk, is a controversial variable regarding the prognosis of recurrence (Cienfuegos et al, 2018;Mörner et al, 2017), but in accordance with some previous findings (Cienfuegos et al, 2018), we found that patients classified as ASA IV were 2-3 times as likely to have early recurrence. Finally, having infectious complications during the first year after surgery plays an important role in early recurrence.…”
Section: Ta B L E 2 (Continued)supporting
confidence: 91%
“…To our knowledge, there is no literature regarding residual tumour classification as a risk factor for recurrence in colon cancer, although it has been related to poor outcomes (Quintana et al, 2016; Yabusaki, Nashimoto, Matsuki, & Aizawa, 2014). Third, ASA grade, a variable related to surgical risk, is a controversial variable regarding the prognosis of recurrence (Cienfuegos et al, 2018;Mörner et al, 2017), but in accordance with some previous findings (Cienfuegos et al, 2018), we found that patients classified as ASA IV were 2-3 times as likely to have early recurrence. Finally, having infectious complications during the first year after surgery plays an important role in early recurrence.…”
Section: Ta B L E 2 (Continued)supporting
confidence: 91%
“…Recent studies have shown that postoperative complications have a negative effect on the oncologic outcome. In particular, infectious complications, surgical intensive care unit admission, and location of anastomosis leakage were associated with negative prognosis [ 7 , 11 , 12 , 23 , 27 - 29 ]. Several studies demonstrated that postoperative complications impact short-term and long-term survival as described above.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding CDC grade V, they found major POCs (IIIb or IV) were significantly associated with OS. Cienfuegos et al 21 examined major POCs (≥CDC grade IIIb) in 950 patients with resected stage I–III colon cancer and identified 51 (5%) cases experienced major POCs. They also found major POCs were associated with long-term OS and disease-free survival (DFS), especially in stage III cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that major POCs evaluated by CDC adversely affect long-term outcomes of CRC patients after resection. 20,21 However, CDC defines the severity of the complication in a single patient according to the most serious complication, and CDC grade alone cannot effectively reflect multiple complications.…”
Section: Introductionmentioning
confidence: 99%